Prolonged T-Piece Spontaneous Breathing Trial and Extubation Outcomes in Patients Received Prolonged Mechanical Ventilation - Tsung-Ming Yang; Yu-Hung Fang; Chia-Hao Chang; Shih-Jiun Lin; Cheng-Chi Liu; David Ming Then Tsai; Chun-Liang Lin; Chieh-Mo Lin; Yung-Chien Hsu (Medicina)
Background and Objectives: Unassisted breathing through a T-piece was the most used spontaneous breathing trial (SBT) in endotracheal intubated prolonged mechanical ventilation (PMV) patients. However, the optimal duration of an SBT in PMV patients remains uncertain. In this study, we compared the extubation outcome between a 12 h T-piece SBT and a 24 h T-piece SBT in PMV patients. Materials and Methods: We reviewed the medical records of PMV patients who were extubated after passing a 12 h or 24 h T-piece SBT. The extubation, weaning, and hospital outcomes between the 12 h T-piece SBT group and the 24 h T-piece SBT group were compared. Kaplan–Meier survival plots and Cox proportional hazard models were used to evaluate the risk of extubation failure between groups. Results: In this study, 120 patients were extubated after passing the 12 h T-piece SBT and 234 patients were extubated after passing 24 h T-piece SBT. Patients in the 24 h T-piece SBT group had higher APACHE II score and lower Glasgow coma scale upon RCC arrival than patients in the 12 h T-piece SBT group. There was no difference in gender, age, or ventilator days before extubation between these two groups of patients. After extubation, patients in the 12 h T-piece SBT group and 24 h T-piece SBT group had similar extubation failure rates within 5 days (26.7% vs. 26.1%, p = 0.904). There was no difference in the RCC weaning rate (85% vs. 85.5%, p = 0.929) and hospital mortality rate (19.8% vs. 21.8%, p = 0.821) between the 12 h T-piece SBT group and the 24 h T-piece SBT group. Subgroup analysis showed that 24 h T-piece SBT was associated with a lower extubation failure rate in PMV patients with myocardial infarction or heart failure, but not in older PMV patients or those with cerebrovascular disease. Conclusions: The extubation and weaning outcomes were similar in PMV patients extubated after passing 12 h T-piece SBT or 24 h T-piece SBT.